The Effect of Chronic Humanin Administration on Apoptosis and Inflammation in STZ-Induced Cardiac Dysfunction in Mouse Model - Bulut, F.; Bilgin, B.; Hekim, M. G.; Kelestemur, M. M.; Adam, M.; Ozgen, A.; Ozcan, M. (Wiley, 2022)
[Abstract Not Available]